The Major Components of Essential Oils from Ocimum Species of Tanzanian Origin (The East and Central African Journal of Pharmaceutical Sciences, 2020)
Steam distillation of fresh leaves and flowers of Ocimum canum Sims (Syn. O. americanum L.) from two localities, Kimara and Muhimbili, gave essential oils in yields of 0.6% and 0.9% respectively. Leaves and flowers of O. gratissimum L. gave a 0.26% yield while that of O. suave Wilid was 0.6%. The oils were analyzed by GC and GC-MS. The oil of 0. gratissimum and that of O. suave had eugenol as their major component. Oils of O. canum from the two localities. differed considerably in their chemical composition. The oil from plants collected in Kimara gave 1,8-cineole as the major component while ocimenoyl oxide was the major component of the oil from Muhimbili plants. Ocimenoyl oxide which constitutes 60% of the oil has not been reported previously in the genus.
Keywords: Ocimum canum, 0. americanum, Labiatae, ocimenoyl oxide